НОМЕНКЛАТУРНА ЕЛІТА УКРАЇНИ ТА СОЦІАЛЬНО0 ПОЛІТИЧНІ ДЖЕРЕЛА ЇЇ ФОРМУВАННЯ У 1920–19300Х РР. (Zaporizhzhia Historical Review, 2021)
The article is dedicated to the determination issue of Soviet Ukraine government’s nature. The author makes conclusion it was represented by nomenclative elite, having certain authoritative power but depending on central elite. The main sources of nomenclative elite formation were Bolsheviks – natives of Ukraine, Soviet Party officials sent from Russia and representatives from other parties in Communist Party (Bolshevik) of Ukraine.